Peran Pendidikan Vokasional dalam Penguatan Human Capital di Era Industri 5.0 : Studi pada Peserta Didik di SMK Entrepreneur Indonesia Sragen - Novariani Indri Utami; Mintasih Mintasih; Salman AT (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2025)
This study aims to analyze the role of vocational education in strengthening human capital in the era of Industry 5.0 through a case study of students at SMK Entrepreneur Indonesia Sragen. Vocational education is a crucial component in developing competent, adaptive, and innovative human resources in the face of technological disruption and changing job market needs. Using a descriptive-qualitative approach, this study examines how the implementation of a competency-based curriculum, entrepreneurship training, and collaboration with the industrial world can improve the quality of human capital. The results show that vocational education at SMK Entrepreneur Indonesia Sragen successfully improves students' technical abilities, digital skills, and entrepreneurial spirit, thus better preparing them to face the demands of the world of work in the era of Industry 5.0. In addition, policy support, teacher training, and technology-based learning facilities also strengthen learning outcomes. This study confirms that vocational education plays a strategic role in producing productive, creative, and globally competitive graduates. Strengthening human capital through vocational education is a key factor in accelerating Indonesia's economic transformation towards an intelligent and highly competitive society in the digital era.